The Role of Knowledge Management and Green Innovation in Sustainable Performance - Cong, Phan The (iRASD Journal of Management, 2023)
This study investigates the function of knowledge management (KM) in fostering sustainable performance through green innovation actions and strategies. Data were gathered for the study from managers at several organizations in services and manufacturing industry. In order to examine how knowledge management processes, which include knowledge creation, acquisition, sharing, and application, affect the advancement of green innovation actions and green innovation strategies, and sustainable performance using structural equation modeling (SEM) was used. The findings indicate that knowledge management has a substantial and positive impact on both green innovation and sustainable performance. A sub-dimensional investigation further revealed that, with the exception of knowledge acquisition, which demonstrated insignificant effects on sustainable, all other paths showed statistically significant outcomes. Furthermore, the study underscores the universal significance of KM for firms.